Planet Earth, Plants, People & Pollution: A Review - Singh, Anand (Academic Voices: A Multidisciplinary Journal, 2018)
Purity of nature and all-natural resources for living creature is an utmost necessity for future existence and livingness of flora and fauna. Balance development with sustainability is also an urgent need for better future on the planet earth. It is impossible to imagine a safe and clean environment for people on this beautiful, natural world where all-natural resources surrounding us are being polluted each and every moment. No place on this planet has remained left to live a healthy and happy life.